2022
DOI: 10.55761/abclima.v30i18.14908
|View full text |Cite
|
Sign up to set email alerts
|

Ilhas de calor urbanas de superfície, ondas de calor e de frio no município do Rio de Janeiro – RJ (2015 - 2019)

Abstract: O objetivo do artigo foi analisar as relações entre a ocorrência de ondas de calor e ondas de frio e as ilhas de calor de superfície no município do Rio de Janeiro - RJ. As ondas foram definidas a partir da duração mínima de três dias consecutivos, com temperaturas superiores (inferiores) aos percentis 95 (5%), para as ondas de calor (frio). Dados de temperatura média diária de sete estações no município foram coletados e sistematizados, entre 2015 e 2019. Quanto às ilhas de calor de superfície, foram empregad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The years 2014, 2015 and 2019 were very hot compared with the average in Brazil. During these years, HW events affected a large part of the Brazilian territory, mainly in the Southeast (Mendes et al, 2022; Oliveira et al, 2021) and South (Alves et al, 2016; Cardoso et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The years 2014, 2015 and 2019 were very hot compared with the average in Brazil. During these years, HW events affected a large part of the Brazilian territory, mainly in the Southeast (Mendes et al, 2022; Oliveira et al, 2021) and South (Alves et al, 2016; Cardoso et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In studying the occurrence of HWs and cold waves (CWs) in 2015–2019 in Rio de Janeiro State, Mendes et al (2022) reported that 2015 and 2019 had the highest frequency of HWs. Bitencourt et al (2020) investigated CWs and HWs from 1961 to 2016 in Brazil.…”
Section: Resultsmentioning
confidence: 99%